2021
DOI: 10.1016/j.ebiom.2021.103208
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomes and gut microbiome induced insulin resistance in mice exposed to intermittent hypoxia: Effects of physical activity

Abstract: Background Gut microbiota (GM) contribute to obesity and insulin resistance (IR). Obstructive sleep apnea (OSA), characterized by intermittent hypoxia (IH), promotes IR and alters GM. Since circulating exosomes are implicated in IR, we examined the effects of IH and physical activity (PA) in mice on GM, colonic epithelium permeability, systemic IR, and plasma exosome cargo, and exosome effects on visceral white adipose tissues (vWAT) IR. Methods C57BL/6 mice were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 120 publications
0
37
0
Order By: Relevance
“…Tightening the intestinal mucosal barrier also plays an important role in suppressing systemic inflammation and consequent neuroinflammation. Numerous results suggest that the gut microbiome modulate the intestinal barrier function [149][150][151]. In this context, butyrate has been shown to enhance the intestinal barrier function through maintenance of the expression of tight junction proteins including claudins, occludin, and zonula occludens protein-1 (ZO-1) [152], and an animal study has demonstrated that oral administration of C. butyricum or butyrate reduces intestinal injury associated with severe acute pancreatitis [153].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Tightening the intestinal mucosal barrier also plays an important role in suppressing systemic inflammation and consequent neuroinflammation. Numerous results suggest that the gut microbiome modulate the intestinal barrier function [149][150][151]. In this context, butyrate has been shown to enhance the intestinal barrier function through maintenance of the expression of tight junction proteins including claudins, occludin, and zonula occludens protein-1 (ZO-1) [152], and an animal study has demonstrated that oral administration of C. butyricum or butyrate reduces intestinal injury associated with severe acute pancreatitis [153].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Furthermore, the ratio of pAKT/tAKT as indicator of insulin sensitivity remained unaltered after exposure to any of the EVs, irrespective of whether the cells had been exposed to IH or RA. Such findings, which are not aligned with the fact that circulating EVs in patients with OSA induce insulin resistance [ 21 , 55 ], suggest that other cells (for example, platelets, lymphocytes, etc.) and possibly other factors that are present in OSA but not reflected in the in vitro IH exposures (e.g., sleep fragmentation) may be operationally involved.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have highlighted the potential contributions of EVs to human diseases, and OSA is not an exception. Studies on the involvement of EVs in the emergence of endothelial cell dysfunction and adipocyte insulin resistance in both patients suffering from OSA and animal models of OSA have provided robust initial evidence supporting such critical roles [ 9 , 21 , 28 , 55 , 64 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. EV cargo is altered in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…This alteration causes intestinal barrier dysfunction, secretory deficiency of incretin in the intestine, and activation of chronic inflammation. These changes worsen the conditions of IR and cause NAFLD and diabetes mellitus [64][65][66]. Short-chain fatty acids produced by the breakdown of dietary fiber caused by intestinal bacteria promote energy consumption and increase appetite-suppressing hormones [67].…”
Section: Treatment Of Irmentioning
confidence: 99%